2011
DOI: 10.1021/jm1016285
|View full text |Cite
|
Sign up to set email alerts
|

Design of Novel Neurokinin 1 Receptor Antagonists Based on Conformationally Constrained Aromatic Amino Acids and Discovery of a Potent Chimeric Opioid Agonist-Neurokinin 1 Receptor Antagonist

Abstract: A screening of conformationally constrained aromatic amino acids as base cores for the preparation of new NK1 receptor antagonists resulted in the discovery of three new NK1 receptor antagonists, 19 [Ac-Aba-Gly-NH-3′,5′-(CF3)2-Bn], 20 [Ac-Aba-Gly-NMe-3′,5′-(CF3)2-Bn] and 23 [Ac-Tic-NMe-3′,5′-(CF3)2-Bn], which were able to counteract the agonist effect of substance P, the endogenous ligand of NK1R. The most active NK1 antagonist of the series, 20 [Ac-Aba-Gly-NMe-3′,5′-(CF3)2-Bn], was then used in the design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 62 publications
0
61
0
Order By: Relevance
“…The cis / trans ratio of the amide bond between residue 4 and the C-terminal benzylamine moiety in lead compound 4 was investigated by NMR analysis and was estimated to be 35:65. Results obtained by molecular modeling also confirmed one of the three lowest energy conformations in the NK1R pharmacophore to adopt the cis amide geometry, 24 and hence this orientation could be important for NK1R activity. In an attempt to increase the cis / trans ratio, a N - i Bu group was used instead of the N -Me motif.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The cis / trans ratio of the amide bond between residue 4 and the C-terminal benzylamine moiety in lead compound 4 was investigated by NMR analysis and was estimated to be 35:65. Results obtained by molecular modeling also confirmed one of the three lowest energy conformations in the NK1R pharmacophore to adopt the cis amide geometry, 24 and hence this orientation could be important for NK1R activity. In an attempt to increase the cis / trans ratio, a N - i Bu group was used instead of the N -Me motif.…”
Section: Resultsmentioning
confidence: 64%
“…The in vitro biological evaluation of 4 showed that combination of the two components gratifyingly resulted in good binding affinity for both opioid and NK1R receptors. 24 Furthermore, the compound showed antinociceptive activity after intravenous administration in vivo , and hence the hybrid structure proved, similarly to the parent opioid sequence Dmt-D-Arg-Aba-Gly-NH 2 7 , 29 capable of crossing the blood-brain barrier (BBB). Unfortunately, hybrid 4 still produced analgesic tolerance in naive animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Both compounds have a N -methylated amide group in the C-terminal NK1 pharmacophore, which is essential for affinity and antagonism at the NK1 receptor. 1 Whereas secondary amide groups adopt exclusively a trans conformation, tertiary amides exist as a mixture of cis and trans isomers with a reduced activation energy for rotation. 17 Since a large percentage of cis isomers (18–22%) was found in an earlier study of NK1-ligands, this configuration might be important for activity.…”
Section: Resultsmentioning
confidence: 99%
“…19,20,26 Moreover, the in vivo studies showed activity in acute pain 26 as well as in neuropathic pain models. 20 The potent analgesic responses after intravenous (i.v.)…”
mentioning
confidence: 99%